1994
DOI: 10.1046/j.1471-4159.1994.63031143.x
|View full text |Cite
|
Sign up to set email alerts
|

Potassium and Taurine Release Are Highly Correlated with Regulatory Volume Decrease in Neonatal Primary Rat Astrocyte Cultures

Abstract: Neonatal rat primary astrocyte cultures were swollen by exposure to hypotonic buffer. Using an electrical impedance method for determination of cell volume coupled with on‐line measurements of efflux of radioactive ions or amino acids, we have investigated the role of K+ (using 86Rb), taurine, and d‐aspartate (an analogue of glutamate) in regulatory volume decrease (RVD). Addition of 1 mM quinine, 10 µM nimodipine, 100 µM BAPTA‐AM, 10 µM trifluoperazine, or a calcium‐free buffer significantly (p < 0.0001) inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(43 citation statements)
references
References 28 publications
2
40
1
Order By: Relevance
“…In the current study, the characteristics of OTR were found to be similar to other studies using C6 glioma cells and astrocytes, in terms of increase in OTR rate following hypoosmotic exposure and the time taken to reach the maximal taurine release rate [43,44]. Furthermore, OTR in the current study demonstrated a similar pharmacological profile to that exhibited by other neuronal cells: the anion channel blockers NPPB (100 lM) and DIDS (100 lM) decreased the OTR rate by approximately the same percentage as previously observed in astrocytes [45].…”
Section: Anion Channel Blockers Decrease the Otr Ratesupporting
confidence: 86%
“…In the current study, the characteristics of OTR were found to be similar to other studies using C6 glioma cells and astrocytes, in terms of increase in OTR rate following hypoosmotic exposure and the time taken to reach the maximal taurine release rate [43,44]. Furthermore, OTR in the current study demonstrated a similar pharmacological profile to that exhibited by other neuronal cells: the anion channel blockers NPPB (100 lM) and DIDS (100 lM) decreased the OTR rate by approximately the same percentage as previously observed in astrocytes [45].…”
Section: Anion Channel Blockers Decrease the Otr Ratesupporting
confidence: 86%
“…In some cell types, activation of swelling-induced taurine efflux requires extracellular Ca 2ϩ (514,1036), whereas in others, it occurs (674, 733), or is even improved (435,498), in the absence of extracellular Ca 2ϩ (see also sect. VB).…”
Section: Mechanisms Of Activation Of the Taurine Efflux Pathwaymentioning
confidence: 99%
“…Swelling of the end feet of astrocytic perivascular processes may also lead to altered cerebral blood flow [71]. Cell swelling is rapidly followed by regulatory volume decrease and the release of organic osmolytes, of which the amino acid taurine is of especial interest [72][73][74][75]. Taurine has previously been shown to increase accumbal dopamine levels, and appears to be a key component in ethanol induced dopamine release [76][77][78].…”
Section: Astrocytic Cell Swellingmentioning
confidence: 99%